Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Simulating Spatial Variation of Soil Carbon Content in the Yellow River Delta: Comparative Analysis of Two Artificial Neural Network Models - Chen Wang; Yuan Cui; Ziwen Ma; Yutong Guo; Qian Wang; Yujiao Xiu; Rong Xiao; Mingxiang Zhang (Wetlands, 2020)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)